KEDISIPLINAN KERJA PADA KARYAWAN DI PT. BUMI RAYA UTAMA GROUP PONTIANAK - Rupia, Rupia; Zaklin, Zaklin; Salfarini, Eligia Monixa (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The purpose of practical work (internship) is one of the most important efforts in supporting the development of employee discipline. One of the approaches used is Merdeka Belajar Kampua Mengajar (MBKM) which emphasizes improving work discipline, and work cleanliness and tidiness. This study aims to evaluate the implementation of MBKM-based practical work (internships) in Pontianak, West Kalimantan. The method used in lean method research with the concept can provide significant benefits in improving work discipline, in supporting the growth and sustainability of MBKM in Pontianak, West Kalimantan.